Clinton Presba Anderson papers - Anderson, Clinton Presba, 1895-1975.
Correspondence, memoranda, speeches, hearing transcripts, reports, and other papers pertaining to Anderson's service in Congress (1941-1973). Subjects include agriculture, civil rights, conservation and natural resources, education, health care, Indian affairs, nuclear energy, poverty, and the Vietnam War. Includes Anderson's files as a member of the Joint Committee on Atomic Energy pertaining, in part, to the U.S. Atomic Energy Commission, Lewis L. Strauss, and the security investigation of J. Robert Oppenheimer. Other files relate to the Nuclear Test Ban Treaty of 1963, Atoms for Peace Awards proposed by Dwight D. Eisenhower to encourage international cooperation in the use of nuclear energy, the Senate Committee on Aeronautical and Space Sciences, and the relief program following the Alaskan earthquake, 1964.
Correspondents include Charles F. Brannan, Dennis Chavez, Wilbur J. Cohen, Gordon E. Dean, Carl Atwood Hatch, Hubert H. Humphrey, Henry M. Jackson, Lyndon B. Johnson, Warren G. Magnuson, Mike Mansfield, Joseph McCarthy, Brien McMahon, Joseph Manuel Montoya, James E. Murray, Richard B. Russell, Glen Theodore Seaborg, Sargent Shriver, Lewis L. Strauss, Stuart Symington, Harry S. Truman, and Stewart L. Udall.
U.S. senator and representative from New Mexico and U.S. secretary of agriculture.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brannan, Charles F. -- 1903- -- Correspondence; Chavez, Dennis, -- 1888-1962 -- Correspondence; Cohen, Wilbur J. -- 1913-1987 -- Correspondence; Dean, Gordon E., -- 1905-1958 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969.; Hatch, Carl Atwood, -- 1889-1963 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Jackson, Henry M. -- 1912-1983 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Magnuson, Warren G. -- 1905-1989 -- Correspondence; Mansfield, Mike, -- 1903-2001 -- Correspondence; McCarthy, Joseph, -- 1908-1957 -- Correspondence; McMahon, Brien, -- 1903-1952 -- Correspondence; Montoya, Joseph Manuel, -- 1915-1978 -- Correspondence; Murray, James E. -- 1876-1961 -- Correspondence; Oppenheimer, J. Robert, -- 1904-1967.; Russell, Richard B. -- 1897-1971 -- Correspondence; Seaborg, Glenn Theodore, -- 1912- -- Correspondence; Shriver, Sargent, -- 1915-2011 -- Correspondence; Strauss, Lewis L; Strauss, Lewis L. -- Correspondence; Symington, Stuart, -- 1901-1988 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Udall, Stewart L. -- Correspondence; U.S. Atomic Energy Commission; United States. -- Congress; United States. -- Congress. -- Joint Committee on Atomic Energy; United States. -- Congress. -- Senate. -- Committee on Aeronautical and Space Sciences; Atoms for Peace Awards, inc; Nuclear Test Ban Treaty -- (1963); Aeronautics; Agriculture; Civil rights; Communism -- United States; Conservation of natural resources; Disaster relief -- Alaska; Earthquakes -- Alaska; Education -- United States; Energy policy -- United States; Indians of North America -- Government relations; International cooperation; Medical care -- United States; Medical policy -- United States; Natural resources -- United States; Nuclear energy; Nuclear weapons -- Testing; Poverty; Subversive activities -- United States; Vietnam War, 1961-1975 -- United States; United States -- Politics and government -- 1933-1945.; United States -- Politics and government -- 1945-; Cabinet officers; Representatives, U.S. Congress -- New Mexico; Senators, U.S. Congress -- New Mexico